Sedimentary phosphorus record from the Oman margin : New evidence of high productivity during glacial periods - Tamburini, Federica; Föllmi, Karl B.; Adatte, Thierry; Bernasconi, Stefano M.; Steinmann, Philipp (My University, 2003)
The northern region of the Arabian Sea is one of the biologically most fertile regions of the world oceans, with present productivity rates varying between 150 and 2500 mgC/m2 × day [ Madhupratap et al., 1996 ]. This is related to the influence of the southwesterly summer monsoon which causes vigorous upwelling along the Oman margin. Upwelling ceases during northeasterly winter monsoon activity; productivity rates, however, remain relatively high (about 800 mgC/m2 × day), related to deep water mixing [ Madhupratap et al., 1996 ]. The goal of this study is to verify if during the last glacial period, a period in which winter monsoon conditions prevailed, productivity rates were similarly high. With an analysis of phosphorus phases, stable nitrogen isotopes, organic matter content, and bulk mineralogy of the upper 10 m of the cores of ODP Hole 724C (corresponding to the last 140,000 years, sample resolution is ∼5 kyr), we provide new evidence of high productivity during this last glacial period (marine isotopic stages 2, 3, and 4). This was probably related to the combined effect of (1) increased eolian input of iron-containing dust due to dryness on the adjacent continent and stronger winter monsoon, and (2) regeneration and diffusion of dissolved phosphorus from the sediments to the water column due to variations in the position and intensity of the Oxygen Minimum Zone. These findings suggest that there is no one-to-one relationship between summer monsoon activity and productivity, which emerges to be a quasi-persistent phenomenon across glacial and interglacial stages.
Keywords: phosphorus; Omanmargin; monsoon; productivity